Text validation: Overlooking consistency effect discrepancies. - Singer, Murray; Spear, Jackie; Rodrigo-Tamarit, Maria (Memory & Cognition, 2023)
The consistency effect, prevalent in the text comprehension literature, comprises longer reading times for inconsistent than equivalent consistent text continuations. It is widely interpreted as reflecting readers' effective "validation" of text coherence. However, there are also numerous phenomena of readers' deficient validation, sometimes collectively labelled "misinformation effects." This study asked whether readers become consciously aware of the text discrepancies diagnosed by the consistency effect. Experiment 1 scrutinized (a) conspicuous conceptual inconsistencies and (b) character-trait inconsistencies. It replicated the consistency effect both at a critical target sentence and at a subsequent sentence (spillover). Experiment 2 replaced self-paced reading with consistency judgments about the target sentences. The subjects overlooked almost half of the inconsistencies, thus denying that readers reliably become aware of consistency-effect discrepancies. In Experiment 3, the former target sentences were reframed as explicit questions. Accuracy for inconsistencies was statistically indistinguishable from accuracy for consistent targets, favoring the interpretation that Experiment 2 subjects overlooked known, encoded discrepancies. The results are interpreted with reference to Kintsch's (Psychological Review, 95, 163-182, Kintsch, 1988; Comprehension. New York: Cambridge University Press, Kintsch, 1998) construction-integration model, a refinement of which adds an immediate, passive stage of validation processing to construction and integration. It is proposed that passive validation affords the detection of text inconsistencies that do not reach the level of readers' conscious awareness.